(untitled) (Web of Teachers: Inderscience Research, 2025)
Women who have experienced pressure and violence often suffer from severe psychological trauma that can affect their emotional, social, and cognitive well-being. Effective psychological counseling methods play a crucial role in helping these women regain their confidence, cope with trauma, and reintegrate into society. This article examines various counseling approaches, including cognitive-behavioral therapy (CBT), trauma-focused therapy, empowerment-based interventions, and group therapy. By analyzing the effectiveness of these methods, the paper aims to provide insights into best practices for supporting survivors of violence.